1970
DOI: 10.1139/v70-465
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Diquaternary aromatic compounds. III. Syntheses and reactions of polyalkyltetralones and derivatives

Abstract: A new synthesis is reported of polyalkyltetralones based on reactions of a,a-dialkylarylacyl chlorides with branched alkenes in the presence of stannic chloride. The following were synthesized by this method: 1,1,4,4-tetramethyl-2-tetralone (7a), 1 ,I ,3,4,4-pentamethyl-2-tetralone (7b), 1,1,4,4,6-pentamethyl-2-tetralone (7c), 1,l-diethyl-4,4-dimethyl-2-tetralone (7d), and 3-keto-l,l,4,4-tetramethyl-1,2,3,4-tetrahydrophenanthrene (7e). Cyclialkylation of toluene with 2,2,5,5-tetramethyltetrahydrofuranone yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It has been reported that conversion of a keto-tetrahydronaphthalene to a dihydronaphthalene can successfully be performed using POCl 3 /pyridine . Thus, reaction of keto-tetrahydronaphthalene 22 , prepared in four steps and 50% overall yield from p -tolylacetic acid, with 14 using AlCl 3 (4.0 equiv) afforded 23 in 62% yield. Olefination of 23 with methyltriphenylphosphonium ylide afforded olefin 24 in 57% yield.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that conversion of a keto-tetrahydronaphthalene to a dihydronaphthalene can successfully be performed using POCl 3 /pyridine . Thus, reaction of keto-tetrahydronaphthalene 22 , prepared in four steps and 50% overall yield from p -tolylacetic acid, with 14 using AlCl 3 (4.0 equiv) afforded 23 in 62% yield. Olefination of 23 with methyltriphenylphosphonium ylide afforded olefin 24 in 57% yield.…”
Section: Resultsmentioning
confidence: 99%